ISSUES, CHALLENGES, AND PROSPECTS OF THE CHOICE BASED CREDIT SYSTEM (CBCS) - Chauhan, Rajesh Kumar; Pathak, Ashish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Choice Based Credit System (CBCS) represents a progressive approach to higher education, emphasizing flexibility, student autonomy, and the integration of interdisciplinary, intra-disciplinary, and skill-based courses. CBCS aims to integrate Indian higher education with global academic frameworks, by implementing a uniform grading system and facilitating credit transfer mechanisms .Students performance is evaluated through Continuous and Cumulative Grade Point Average (CGPA), ensuring the comprehensive evaluation of academic performance. However, despite its potential advantages, the implementation of CBCS faces significant challenges, including infrastructure constraints, increased faculty workload, and the need for standardized implementation across institutions. This paper critically examines the issues, challenges, and future prospects of the CBCS system in the Indian education context.